Integrating fishers’ knowledge contributions in Marine Science to tackle bycatch in the Bay of Biscay - Cazé, Cosma; Réveillas, Justine; Danto, Anatole; Mazé, Camille (Frontiers in Marine Science, 2022)
The issue of bycatch is raising considerable political, mediatic and scientific attention. Bycatch is one of the main causes of at-sea mortality for small cetacean species and for seabirds. Scientists are raising alerts regarding the potential effects on the structure of the ecosystem, increasingly aiming for research-action. Decision-makers are facing a political trade-off, with increasing pressure from the European Commission and international nongovernmental organizations to implement mitigation measures such as space-time closure of the fisheries, which could present a risk of altering the well-being of the fishing industry in the short-term. The process of co-creation of knowledge on bycatch is key to understand better the fishers-species interactions and to develop regulations that are adapted to local specificities, towards an adaptive and inclusive socio-ecosystem-based management of the fisheries. But the knowledge co-creation process is hindered by tensions between the interests of stakeholders, the climate of mistrust, dense media coverage and power asymmetries between actors. In parallel, the fast rate of biodiversity degradation is calling for the rapid development of regulations. Understanding the complex system dynamics highlighted by these conflicts requires an analysis of the socio-political dimension of the interactions between fisheries and marine biodiversity. Based on a series of ethnographic interviews with the different stakeholders involved in the bycatch mitigation projects in the Bay of Biscay, this paper explores how co-creating knowledge through conflict and collaboration between researchers and fishers can generate collective learning for bycatch mitigation policies. We adopt an epistemological approach, with the objective to promote transparency in the exchange between researchers and fishers and to inform decision-making at various scales of governance. We argue that co-creation of knowledge on bycatch should not aim for consensus. We conclude that acknowledging the presence of conflicts between the stakeholders, and understanding their roots and their impact on the co-design process can allow identifying factors of path-dependency hindering the adaptive capacity of institutions. Moreover, we highlight the key role of the fishers’ representative bodies in knowledge co-creation, and the importance to improve our understanding of fishers' perception of their political representation.